Investigation of retinal thickness using optical coherence tomography: a prospective phenotype study of patients with inherited ataxia - Bogdanova-Mihaylova, Petya Petrova (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Inherited cerebellar ataxias (CA) are clinically and genetically heterogeneous disorders. A diverse range of ophthalmic abnormalities have been reported in different subtypes of CA and, although visual symptoms are not always recognised, both afferent and efferent pathways can be affected. Abnormal retinal nerve fibre layer (RNFL) thickness to a degree measurable by optical coherence tomography (OCT) has been documented in common trinucleotide repeat disorders and in association with SACS (Sacsin Molecular Chaperone) gene mutations. Data on RNFL findings in other non-Friedreich’s ataxia (FRDA) cohorts are scarce and little is known about retinal changes over time in CA. My main hypothesis was that retinal changes in inherited ataxias are more common than previously thought, that OCT may play a role in distinguishing different types of ataxias, and that RNFL structural changes have a functional correlate, and thus, RNFL thickness measured with OCT has the potential to become a useful biomarker in CA. The specific aims of the study were to characterise the clinical phenotypes and, using OCT, retinal findings associated with different types of inherited ataxias; to determine the pattern of retinal changes and their association with disease duration and functional disability quantified with the Scale for the Assessment and Rating of Ataxia (SARA) and to determine if retinal changes are evident over time. In order to test this hypothesis, I performed an observational phenotype study of 131 patients with different types of determined or suspected genetic ataxia, and 7 asymptomatic first- degree relatives of affected individuals. Clinical assessment using a standardised approach, including detailed neurological examination was performed to characterise the phenotype of rare ataxic syndromes. Best-corrected visual acuity was measured using Snellen chart and OCT was performed to document retinal findings at baseline and, when possible, at an interval to investigate if retinal changes are evident over time. Functional disability was assessed using SARA score and correlations with OCT measurements were assessed. Throughout the course of the study, significant and most marked average RNFL thinning with predominant superior quadrant involvement was found in the FRDA group. Although the average RNFL thickness in the largest SPG7-associated spastic ataxia cohort subjected to OCT to date was no statistically different from controls, the temporal RNFL thickness was reduced in the patient group (p<0.05). A distinct thickening of RNFL was found in individuals with ARSACS. Previously not reported optic neuropathy was found in DDHD2- , ANO10-, and SAMD9L-associated phenotypes, while no RNFL changes were detected in individuals with AOA1, CANVAS, AIFM1- and MT-ATP6-related disease. As expected, among the group of autosomal dominant CA (ADCA), retinal abnormalities were found in SCA7, contrary to SCA1, 2, 3, 6, 14, and EA2. There was a correlation between RNFL thickness and SARA score in the FRDA group, but no association was found in the SPG7– associated cases. Follow-up evaluation showed significant decline in most OCT parameters in FRDA as well as in average and temporal RNFL thickness measurements in the SPG7 cohort simultaneously with disability progression, while a tendency to progressive RNFL thinning was documented in SCA1, but not in SCA3. In contrast, a tendency to increased macular and foveal thickness over time was seen in ARSACS, but average RNFL thickness or disease progression was not observed. In conclusion, optic neuropathy is common in various subtypes of ataxia despite their clinical heterogeneity even in the absence of decreased visual acuity. Characteristic retinal changes, found predominantly in spastic ataxia phenotypes, indicate that OCT is a sensitive marker for distinguishing certain genetic ataxias and suggest that this cost-effective technique should be considered part of the routine evaluation in individuals with CA. The longitudinal OCT data showed significant progression rates in some genetic ataxias and imply that OCT has the potential to become a quantifiable biomarker in future therapeutic trials.
APPROVED
Keywords: Optical coherence tomography; OCT; inherited ataxia; retinal nerve fibre layer; RNFL